Особенности атакующих действий высококвалифицированных женщин-боксеров - Гасанова, Саида; Gasanova, Saida (Східноєвропейський національний університет ім. Лесі Українки, 2015)
В теории и методике женского бокса не выявлена четкая концепция изучения закономерностей соревно- вательной деятельности, не разработаны модели наиболее оптимальных действий спортсменок в ринге, результаты экспериментальных и теоретических исследований по данной проблеме в женском боксе немно- гочисленны и трудно поддаются систематизации. Задача работы – изучить особенности атакующих дей- ствий высококвалифицированных женщин-боксеров на основе количественного анализа поединков. Получены данные о количественных показателях атакующих действий спортсменок: о количестве и видах ударов, коэффициентах эффективности ударов. Проанализирована динамика распределения атакующих действий в течении боя. Она у высококвалифицированных женщин-боксеров практически полностью соответствуют одной из наиболее оптимальных тактических схем. У теорії та методиці жіночого боксу не виявлено чіткої концепції вивчення закономірностей змагальної діяльності, не розроблено моделі найбільш оптимальних дій спортсменок у ринзі, результати експериментальних і теоретичних досліджень із цієї проблеми в жіночому боксі нечисленні й важко піддаються систематизації. Завдання роботи – вивчити особливості атакуючих дій висококваліфікованих жінок-боксерів на основі кількісного аналізу поєдинків. Отримано дані про кількісні показники атакуючих дій спортсменок: про кількість і види ударів, коефіцієнти ефективності ударів. Проаналізовано динаміку розподілу атакуючих дій у перебігу бою. Вона практично повністю відповідає одній із найбільш оптимальних тактичних схем. The theory and methodology of female boxing has not revealed a clear concept of studying of regularities of competitive activity, it was not developed the models of the most optimal actions of female athletes in the ring, the results of experimental and theoretical studies on the issue in female boxing are not numerous and difficult to systematize. The objective of the work is to study the peculiarities of offensive actions of highly qualified female boxers on the basis of quantitative analysis of matches. It was obtained the data on quantitative indices of offensive action of athletes: number and types of blows, effectiveness coefficient of blows. It was analyzed the dynamics of distribution of offensive actions during a combat. Dynamics of offensive actions during a combat among highly qualified female boxers practically always corresponds with one of the most optimal tactical schemes.
Peculiarities of Offensive Actions of Highly Qualified Female Boxers
Keywords: женский бокс; атакующие действия; коэффициент эффективности ударов; female boxing; attacking actions; effectiveness coefficient of blows